INNOVATIVE TEACHING METHODS IN HEI IN THE PROCESS OF MASTER’S TRAINING - Stynska, Viktoriia; Prokopiv, Liubov (Mountain School of Ukrainian Carpaty, 2020)
In the article the factors of higher education development that update innovative educational processes are analyzed; the essence of the category «innovation» in relation to higher education is highlighted; the most effective innovative teaching methods in HEI are described in the process of masters training in the specialty 011 Educational, pedagogical sciences (case method, business game, method «Circle of ideas», method «Aquarium», method «Take a position», problem solving method), modeling, audiovisual teaching method, project method, «Decision Tree», etc.). In HEI nowadays,students preparation must be directed to future professional needs of the specialist, must form such a level of professional and general culture, professional competence, which will maintain high professionalism in any sphere of activity. In addition, there must be readiness to acquire new qualifications, retraining in the sphere of pedagogical activity, to constantly update and improve their professional level throughout life. This approach changes not only the content, structure of higher pedagogical education, but also its methods. Realizing that the creation of an innovative educational environment is impossible without introducing a qualitative new content in higher professional education, without increasing the level of scientific and methodological support of the educational process, introduction of innovative technologies and teaching methods, mastering experimental activities. The search for new effective forms and methods of higher pedagogical education is becoming an actual task of HEI that prepare masters of pedagogy:from the development and introduction into the curriculum of new promising disciplines to the introduction of innovative methods. It is concluded that the strategic aim of reforming higher education and science in Ukraine is to create an effective innovative educational environment in HEI, the introduction of modern teaching methods in the social and cultural sphere, management system and labor organization in a market economy. Therefore, only an organic combination of innovative methods with classical, traditional, thoughtful and harmonious combination of different methods for each discipline and each lesson depending on their aim, purpose, specificity will improve the quality and intensity of the educational process in HEI during masters training.